Sieviešu tēlu tipoloģija un funkcionalitāte biļinās, vēsturiskajās dziesmās un balādēs. - Urjupina, Julija (Latvijas Universitāte, 2012)
Darbs ir veltīts sieviešu tēlu tipoloģijas un funkcionalitātes izpētei biļinās, vēsturiskajās dziesmās un balādēs. Autors pēta sieviešu tēlu tipoloģijas un funkcijas pēc to pāradīšanas biežuma biļinās, vēsturiskajās dziesmās un balādēs, kā arī salīdzina un analizē sieviešu tēlu tipus, lai noteiktu to līdzīgas un atšķirīgas pazīmes tekstos. Darbs sastāv no divām daļām. Pirmajā daļā tiek aplūkoti teorētiskie pamatjautājumi un sieviešu tēlu izpētes pakāpe biļinās, vēsturiskajās dziesmās un baladēs. Otrajā daļā tiek analizēti dažādi sieviešu tēli, to darbība, funkcijas un nozīme. Dotais maģistra darbs ieteicams cilvēkiem, kuri ir ieinteresēti krievu folklorā.

The work represents the study of typology and functionality of female images in epics, historical songs and ballads. The author produces a typological and functional analysis of female images on the frequency of operation of their presence in the texts of epics, historical songs and ballads. Then, comparative and analytical analyses are made to identify similarities and differences in the typology of female images. The work is divided into two parts. The first part sets out the basic theoretical issues and degree of scrutiny of women’s images in the epics, historical songs ballads. The second part is a review of various types of female characters, their actions, functions, and significance. This master work is recommended for those who are interested in Russian folklore.
Typology and Functioning of Female Characters in Epics, Historical Songs and Ballads.
Keywords: Filoloģija